2019
DOI: 10.35940/ijrte.d5418.118419
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Friction Stir Welding on Aluminium 3D Printing Materials

Shaik Syahman B. Shaik Abu Bakar*,
Prof. Dr. Safian B. Sharif,
Dr. Mohd Faridh B. Ahmad Zaharuddin

Abstract: This review paper will discuss about the joining process of Aluminium 3D printing materials by using friction stir welding process. Currently, the studies on the joining of 3D printing materials by friction stir welding are very limited. Through this review, the joining materials characteristics such as weld efficiency, hardness and microstructure after friction stir welding process will be discussed to identify the behavior of weld joint materials. Understanding the friction stir welding process on 3D printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Of all the solid-state welding processes evaluated, FSW is by far the most widely used process for joining AM-manufactured Al alloys [37,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. For this process, only studies were found evaluating the weldability of parts produced by the PBF-LB process.…”
Section: Solid State Welding Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all the solid-state welding processes evaluated, FSW is by far the most widely used process for joining AM-manufactured Al alloys [37,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. For this process, only studies were found evaluating the weldability of parts produced by the PBF-LB process.…”
Section: Solid State Welding Processesmentioning
confidence: 99%
“…This heightened presence is attributed to the expectedly greater plastic deformation on the advancing side during the welding process [56]. The influence of the addition of 2 wt% nAl2O3 to the AlSi10Mg during the PBF-LB manufacturing process was evaluated by two studies [58,59]. The obtained results show an increase in the porosity level from 0.07 to 0.10% at low heat input and from 0.06 to 0.16% at high heat input [58].…”
Section: Solid State Welding Processesmentioning
confidence: 99%
See 1 more Smart Citation